OUTSOURCING AND ORGANISATIONAL EFFICIENCY OF ISSUES IN NIGERIA: RIVERS STATE UNIVERSITY AS A CASE STUDY - Favour, Yakie Ebisidor; Tamunomiebi, Dr. M. D. (Journal of Strategic Management, 2020)
Purpose: the main purpose for this article work was to discuss literature on the relationship between outsourcing and organizational efficiency and how to offers a detailed assessment of outsourcing and its implications for organizational operations and functionality. Methodology: this research adopts the descriptive research technique where all the concepts of the study is investigated in line with other scholars has found as it relates to the work. The resource-based theory was adopted as the theoretical foundation for the study, and it offered a strong position in support of the imperatives of focusing on key assets and responsibilities as a way of enhancing organizational efficiency and ultimately competitiveness Findings: The position reached based on the congruence of views, specifies outsourcing as commendable and required for the efficient functioning of organizations today. On this note, it was concluded that the features of cost and organizational operations are efficiently addressed through the adoption of outsourcing practices and behaviour which are strategic and which allow for the organizations focus on its own key and primary functions. Unique contribution to Theory and Practice: The study gave useful perception of rivers state university that the practice of outsourcing should be such that emphasizes more on the additional functions and areas identified as weak or overly costly to the organization. Such features can be addressed through a shift in responsibilities to other organizations which are more proficient and structured for that purpose.